The Clinical Implications of Thyroid Dysfunction and its Association with Dyslipidemia and the Geographical Effect: A Comparative Study from Different Altitudes in Saudi Arabia - Alqahtani, Saif Aboud M (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Thyroid disorder is one of the most prevalent critical issues for public health in clinical practice. Lipid profiles and cardiovascular attenuation are significantly affected by thyroid dysfunction. Thyroid dysfunction related to altitudes (height from sea level) has attracted endocrinologists worldwide. Objectives The current study aimed to investigate the prevalence of thyroid dysfunction and its association with lipid profile among the Saudi population residing at different altitudes and to explore the effect of altitudes on thyroid status. Materials and Methods In this retro cross-sectional study, a large dataset of thyroid hormones and lipid profiles from walk-in patients of both genders doing hormonal and biochemical tests at public labs and government hospital labs from sea level (Jeddah), low altitude (Najran) and high altitude (Asir) were analyzed over the last five years. The data was analyzed using IBM-SPSS version 27. (SPSS Inc., Chicago, IL). Results Subclinical hypothyroidism was the common laboratory finding in all three regions. The overall mean value of TC, LDL-C and TG was significantly high (p<0.05) in the hypothyroidism group in all three regions. A significant positive correlation was observed between lipid profile, lipid ratio and TSH. However, there was a negative correlation between lipid profile, lipid ratio and FT4. On the other hand, HDL-C shows a weak but significant negative correlation with FT4. The risk of developing subclinical hypothyroidism was relatively low in the Asir region (high altitude). However, the risk of developing primary hypothyroidism and subclinical hyperthyroidism was significantly high in the Asir region (high altitudes). In the Najran region, the relative risk of developing subclinical hypothyroidism and primary hypothyroidism was high in comparison to sea level. Conclusion The prevalence of subclinical hypothyroidism with High TC and high LDL-C follows the order: Najran>Jeddah (sea level)>Asir (high altitudes). However, the prevalence of subclinical hypothyroidism with high TG follows the order: Jeddah (sea level)>Najran>Asir (high altitudes). The risk for developing primary hypothyroidism and subclinical hyperthyroidism was high at high altitudes.
Keywords: Thyroid dysfunction; Lipid profile; Lipid ratio; High altitudes; Sea level; Hypothyroidism; Hyperthyroidism